2020
DOI: 10.1007/s00264-020-04636-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on patients suffering from musculoskeletal tumours

Abstract: Background The aim of the current study was to evaluate the impact of the coronavirus disease (COVID-19) pandemic on musculoskeletal tumor service by conducting an online survey of physicians. Methods The survey was conducted among the members of the ISOLS (International Society of Limb Salvage) and the EMSOS (European Musculo-Skeletal Oncology Society). The survey consisted of 20 questions (single, multiple-response, ranked): origin and surgical experience of the participant (four questions), potential disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 16 publications
0
48
0
1
Order By: Relevance
“…Treatment interruptions (postponement or cessation) were uncommon for patients in our study, however, these decisions were understandably perceived with uncertainty among some patients undergoing palliative treatment. An international survey of 149 physicians across five continents also reported reductions in all treatments including surgery, radiotherapy and chemotherapy for patients with musculoskeletal tumours [24]. Notably, palliative chemotherapy and radiotherapy were stopped or delayed in 20% and 17% of cases, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment interruptions (postponement or cessation) were uncommon for patients in our study, however, these decisions were understandably perceived with uncertainty among some patients undergoing palliative treatment. An international survey of 149 physicians across five continents also reported reductions in all treatments including surgery, radiotherapy and chemotherapy for patients with musculoskeletal tumours [24]. Notably, palliative chemotherapy and radiotherapy were stopped or delayed in 20% and 17% of cases, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
“…An international survey of 149 physicians across five continents also reported reductions in all treatments including surgery, radiotherapy and chemotherapy for patients with musculoskeletal tumours [24]. Notably, palliative chemotherapy and radiotherapy were stopped or delayed in 20% and 17% of cases, respectively [24]. While the authors concluded that significant harm (pain, morbidity, loss of function) could be caused by delays to care for musculoskeletal tumours such as sarcomas, the true impact in terms of reduction in COVID-19 risk compared to cancer outcome is unknown [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a difference-in-differences (DID) method by comparing monthly changes to estimate the associations of the COVID-19 outbreak with individuals' healthcare use and spending, and perceived health status between the 2019 to 2020 season and the 2018 to 2019 season ("two seasons" hereafter). Specifically, we estimated equation 1 [28,29] and perceived health status [30][31][32] in the midst of the pandemic. To extend the literature, we provide comprehensive evidence on the changes in healthcare utilization, healthcare spending, and perceived health status during the COVID-19 pandemic using the individuallevel panel data.…”
Section: Methodsmentioning
confidence: 99%
“…This perspective is supplemented by other Italian contributions from Grassi et al, detailing 'The Covid-19 outbreak' [3] as well as 'The chronic of a silent war' by Benazzo and coll [4]. Orthopaedic oncologist Martin Thaler from Austria relays vital information in his paper on the 'Impact of the COVID-19 Pandemic on Patients Suffering from Musculoskeletal Tumours [5].…”
Section: Vikas Khanduja Marius M Scarlatmentioning
confidence: 99%